2006
DOI: 10.1677/joe.1.06768
|View full text |Cite
|
Sign up to set email alerts
|

Conditional expression of hepatocyte nuclear factor-1β, the maturity-onset diabetes of the young-5 gene product, influences the viability and functional competence of pancreatic β-cells

Abstract: Mutations in the gene encoding hepatocyte nuclear factor (HNF)1b result in maturity-onset diabetes of the young-(MODY)5, by impairing insulin secretory responses and, possibly, by reducing b-cell mass. The functional role of HNF1b in normal b-cells is poorly understood; therefore, in the present study, wild-type (WT) HNF1b, or one of two naturally occurring MODY5 mutations (an activating mutation, P328L329del, or a dominant-negative form, A263insGG) were conditionally expressed in the pancreatic b-cell line, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 52 publications
3
24
0
Order By: Relevance
“…This was confirmed at the protein level by western blotting (Welters et al 2006); thus PTP-BL has been established as an HNF1b-sensitive gene product in INS-1 cells.…”
Section: Effects Of Ptp-bl Expression On Ins-1 Cell Growth and Viabilitymentioning
confidence: 64%
See 2 more Smart Citations
“…This was confirmed at the protein level by western blotting (Welters et al 2006); thus PTP-BL has been established as an HNF1b-sensitive gene product in INS-1 cells.…”
Section: Effects Of Ptp-bl Expression On Ins-1 Cell Growth and Viabilitymentioning
confidence: 64%
“…Thus, identification of the proteins that are mutated in patients with MODY can provide important insights into the functional control of b-cell integrity. In this context, we have recently demonstrated that increased expression of the MODY5 gene product, HNF1b, leads to enhanced rates of apoptosis, altered regulation of the cell cycle and inhibition of stimulated insulin secretion in pancreatic b-cells, suggesting that control of HNF1b expression may be important for the regulation of b-cell viability and function (Welters et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] A vast amount of research involving diabetes and complications is focused on areas such as insulin secretion and resistance, pancreatic beta cells, and maintenance of blood glucose levels. 5,6 of this weakened antioxidant defense, the RBCs of these individuals are more prone to oxidant insult and are believed to be less deformable in comparison to RBCs obtained from healthy individuals. Indeed, it has been reported that the RBCs from people with type 2 diabetes are less deformable than those RBCs obtained from healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, HNF1β has also been associated with ovarian clear cell carcinoma (25,26), and mutations in this protein are also responsible for neonatal cholestatic jaundice (27). Thus, in addition to its effect on pancreatic β-cells (5,28,29), HNF1β appears to be involved in normal functioning of many other organs (10,11).…”
mentioning
confidence: 99%